A Conceptual Review on the Relationship between Teacher Self-Efficacy and Organisational Citizenship Behaviour - Choong, Yuen Onn; bin Yunus, Jamal Nordin; Yusof, Hamidah (International Business Education Journal, 2016)
The main objective of this study is to examine the relationship between dimensionality of teacher self-efficacy and organisational citizenship behaviour amongst teachers at government school, Malaysia. Teacher self-efficacy is comprised of personal teaching efficacy and general teaching efficacy. A research issue is highlighted and discussed in detail and thoroughly. A theoretical background for both construct: efficacy theory and organisational citizenship behaviour have been systematically and clearly discussed. Both constructs are also found to be significantly contributed to the school achievement positively. The conceptual framework is also developed based on past empirical arguments. Numerous contributions are pointed out and adequate justification is provided. Past studies revealed and confirmed the relationship between personal teaching efficacy and organisational citizenship behaviour as well as between general teaching efficacy and organisational citizenship behaviour. Hypothesis is formulated that used to achieve research objective.